(untitled) (Proceedings of Voronezh State University. Series: Geology, 2019)
the article presents the results of a comprehensive investigation of the Miocene deposits of the Absheron archipelago’s western part obtained at determining the lithological, mineralogical and elemental composition of rocks by microscopic and laboratory analysis of samples, microfaunistic study, interpretation of geochemical data, comparison of well-logging materials, as well as data of quantitative analysis of morphological parameters of mineral particles and pore space of rocks. Analysis and generalization of the available data made it possible to identify the facial peculiarities and depositional paleoenvironment of the shallow marine shelf. During petrographic investigations, both iron oxide minerals and syngenetic pyrite were identified in the Sarmatian deposits, which indicates a transitional setting typical for shelf areas, but with a predominance of weakly reductive regime. By the nature of geochemical relations’ values, as well as by the presence of anhydride, gypsum, sodium and chlorine in the rocks, the sedimentation basin of Sarmatian and Maykop deposits is characterized by a change of freshwater and brackish-water deposits, with a predominance of the latter in the section. According to the results of a quantitative analysis of the morphological parameters of mineral particles and pore space on the basis of scanning electronic images, the reservoir properties of rocks are determined and a predictive assessment of the prospect of Miocene deposits is given. The presence of sandy-silty, dolomitic and also calcareous-clayey rocks with sufficient reservoir properties, allow us to consider them promising as reservoirs in the section of Miocene deposits, especially for gas saturation.